Recent progress in the performance of HAPG based laboratory EXAFS and XANES spectrometers. Issue 10 (7th August 2020) - Schlesiger, Christopher; Praetz, Sebastian; Gnewkow, Richard; Malzer, Wolfgang; Kanngießer, Birgit
Abstract : New developments in the description and modeling of Highly Annealed Pyrolytic Graphite (HAPG) mosaic crystals have led to the possibility of designing optimized optical solutions for X-ray absorption fine structure (XAFS) spectroscopy. Abstract : New developments in the description and modeling of Highly Annealed Pyrolytic Graphite (HAPG) mosaic crystals have led to the possibility of designing optimized optical solutions for X-ray absorption fine structure (XAFS) spectroscopy. XAFS is a very versatile method that is usually divided into two sub methods: extended X-ray absorption fine structure (EXAFS) and X-ray absorption near edge structure (XANES) spectroscopies, which need different experimental conditions concerning spectral resolving power, energetic bandwidth and number of detected photons. For facilitating XANES and EXAFS spectroscopies with laboratory- and von Hamos-based spectrometers, tailored optics were designed as well as optimized spectrometer components, i.e. an adequate microfocus X-ray source and a pixelated detector, were chosen. This is shown with a demonstration experiment on pure copper foil. In the XANES case a spectral resolving power of E /Δ E ≈ 4000 and an energy bandpass of around 300 eV were achieved with a measurement time of t = 7 min. For EXAFS, the tailored optic has an increased solid angle at moderate spectral resolving power in combination with a large energy bandpass of over 1 keV and a measurement time of t = 250 s for the given copper foil. These optimized solutions pave the way to perform XANES and EXAFS in the laboratory even for diluted samples with analyte concentrations of only a few weight percent or even less in a reasonable time frame of minutes to hours. Spectrometers, that already had an impact on research, especially catalysis research, therefore, made a huge leap in efficiency that prepares them to meet new challenges, not only as a standalone method, but also in combination with high-end synchrotron radiation facility-based XAFS experiments.